Bangladesh, key challenges for the next millennium. - World Bank. Bangladesh Dhaka Office (Dhaka ; Washington, D.C. : World Bank, 1999)
With reference to economic and social conditions of Bangladesh.
Includes statistical tables.
Keywords: Bangladesh -- Economic conditions; Bangladesh -- Social conditions; Bangladesh -- Economic conditions -- Statistics; Bangladesh -- Social conditions -- Statistics